2008
DOI: 10.1261/rna.1108008
|View full text |Cite
|
Sign up to set email alerts
|

Exonucleolysis is required for nuclear mRNA quality control in yeast THO mutants

Abstract: Production of aberrant messenger ribonucleoprotein particles (mRNPs) is subject to quality control (QC). In yeast strains carrying mutations of the THO complex, transcription induction triggers a number of interconnected QC phenotypes: (1) rapid degradation of several mRNAs; (2) retention of a fraction of THO-dependent mRNAs in transcription site-associated foci; and (3) formation of a high molecular weight DNA/protein complex in the 39-ends of THO target genes. Here, we demonstrate that the 39-59 exonucleolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 24 publications
6
49
0
Order By: Relevance
“…Taken together, these results indicate that when mRNA export is inhibited in the mex67-5 strain at the nonpermissive temperature of 37°C, a large fraction of unspliced transcripts normally degraded by NMD are now retained in the nucleus and targeted for turnover by the nuclear exosome. This observation might be linked to the activation of nuclear RNA surveillance by Rrp6p that was previously shown to occur in RNA export mutants (Jensen et al 2001;Libri et al 2002;Strasser et al 2002;Zenklusen et al 2002;Rougemaille et al 2007;Assenholt et al 2008). These results also demonstrate that the export of several unspliced pre-mRNAs out of the nucleus is dependent on the mRNA export factor, Mex67p, as shown previously for the YRA1 pre-mRNA (Dong et al 2007).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Taken together, these results indicate that when mRNA export is inhibited in the mex67-5 strain at the nonpermissive temperature of 37°C, a large fraction of unspliced transcripts normally degraded by NMD are now retained in the nucleus and targeted for turnover by the nuclear exosome. This observation might be linked to the activation of nuclear RNA surveillance by Rrp6p that was previously shown to occur in RNA export mutants (Jensen et al 2001;Libri et al 2002;Strasser et al 2002;Zenklusen et al 2002;Rougemaille et al 2007;Assenholt et al 2008). These results also demonstrate that the export of several unspliced pre-mRNAs out of the nucleus is dependent on the mRNA export factor, Mex67p, as shown previously for the YRA1 pre-mRNA (Dong et al 2007).…”
Section: Resultssupporting
confidence: 85%
“…In our study, we found that upon genetic inhibition of mRNA export, a large proportion of unspliced precursors are now retained within the nucleus and degraded by the action of the nuclear exosome. This observation might reflect the higher nuclear retention of unspliced transcripts in the nucleus, but could also be due to the activation of nuclear surveillance that was previously shown to occur upon inhibition of mRNA export in a variety of mutant backgrounds (Libri et al 2002;Rougemaille et al 2007;Assenholt et al 2008). Such shifts in the turnover pathways of unspliced transcripts reveal the dynamic nature of RNA turnover that is modulated and/or controlled by the activity of the conserved RNA export factor, Mex67p.…”
Section: Discussionmentioning
confidence: 81%
“…This led to the proposal that Rrp47 may promote the Rrp6-mediated degradation of structured RNA. However, Rrp6 lacking the PMC2NT domain shows comparable exonucleolytic activity to the full-length protein on the substrates tested in vitro (Assenholt et al 2008;Wasmuth and Lima 2012). Furthermore, the N-terminal Sas10/C1D domain is able to complement the synthetic lethality of an rrp47Δ rex1Δ mutant but is itself insufficient for the RNA-binding activity of Rrp47 (Costello et al 2011).…”
Section: Introductionmentioning
confidence: 96%
“…Instead, the 39-to-59 exoribonuclease activity of eukaryotic exosomes is achieved by exosome core association with two hydrolytic enzymes: the tenth subunit, Rrp44 or Dis3, and the eleventh subunit, Rrp6 (Briggs et al 1998;Phillips and Butler 2003;Liu et al 2006;Midtgaard et al 2006;Dziembowski et al 2007;Schneider et al 2007;Wang et al 2007;Lorentzen et al 2008b;Bonneau et al 2009). While the activities of budding yeast Rrp44 and Rrp6 have been characterized (Liu et al 2006;Dziembowski et al 2007;Assenholt et al 2008;Callahan and Butler 2008;Bonneau et al 2009;Schaeffer et al 2009;Schneider et al 2009;Callahan and Butler 2010), much less is known about the intrinsic activities of the human paralogs of Rrp44, DIS3 and DIS3L (Staals et al 2010;, or human RRP6.…”
Section: Introductionmentioning
confidence: 99%